Beach slope distribution mapping using UAV in the Cirebon coastal area - Abdurrahman Umar (EDP Sciences, 2021)
The beach slope is usually estimated using the conventional ground survey, causing the availability of this parameter data to be limited in some areas. Meanwhile, this parameter is considered crucial in the study of shoreline changes and coastal area protection as well as other coastal morphodynamic research. The aim of this study is to demonstrate an efficient technique to calculate the beach slope as well as its distribution in an area. In the daily intertidal period, the beach profile is assumed to be a static planar beach state which does not change due to the insignificant effect of erosion and accretion process. First, the shoreline data set was delineated from the tidal-varied orthomosaic using the UAV. The beach slope is then calculated by comparing the difference in tide level with the difference in the horizontal distance of shoreline points along a cross-shore transect at different times. The utilization of UAV allows mapping the shoreline in an area in several different tidal conditions, allowing the distribution of the beach slope also be mapped. This technique was then applied in the Cirebon Coastal Area and found an average beach slope of 0.105 with 0.100 being the slope class with the highest number of distributions. It was also found that due to the presence of mangroves and coastal structures, no slope conditions dominated this area. The result of beach slope calculation using this technique shows suitability with other studies and reveals UAVs’ potential in mapping the beach slope distribution more efficiently.